Briefing: The 2021 Glasgow Climate Pact: steps on the transition pathway towards a low carbon world. Issue 3 (19th August 2022) - Cohen, Robert; Eames, Philip C.; Hammond, Geoffrey P.; Newborough, Marcus; Norton, Brian
Abstract : This briefing reviews progress that was made at the 26th United Nations Climate Change Conference of the Parties (COP26) held in Glasgow, Scotland, UK over 1–12 November 2021. The context of the global climate change challenge is outlined, along with the aspirations of the major participating international groups. An overall balance sheet is provided that gives an assessment of the achievements and disappointments in the outcomes of COP26. This assessment sets a backdrop to what needs to be achieved when the Parties next meet at COP27 in Sharm El-Sheikh, Egypt in 2022 to address both immediate and longer-term climate change mitigation, adaptation and climate finance.